Improving the interest of high-school students toward chemistry by crime scene investigation. Issue 2 (23rd March 2018) - Basso, A.; Chiorri, C.; Bracco, F.; Carnasciali, M. M.; Alloisio, M.; Grotti, M.
Abstract : Improving the interest of high-school students towards chemistry (and science in general) is one of the goals of the Italian Ministry of Education. To this aim, we designed a context-based activity that actively involved students in six different laboratory experiences interconnected by a case study of the murder of Miss Scarlet, from the famous game Clue. Key points of the activity were: the interest aroused by the subject of crime scene investigation; the direct involvement of the students in all stages of the work (from the realization of the experiments to the resolution of the case); the use of a multidisciplinary approach for addressing a complex scientific problem; the work in chemical laboratories with modern instrumentation; the team work and the supervision by young tutors. To verify the hypothesis that such a multidisciplinary activity could foster the interest for the discipline, an evaluation was performed using a self-report questionnaire designed to assess changes in the situational interest raised by the internship. It was found that the activity significantly increased interest and attitude toward chemistry, mainly for students with lower scores in pleasure for the study of chemistry, self-efficacy and self-concept in chemistry.